Concurrent Angioplasty Balloon Placement for Stent Delivery through Jugular Venous Bulb for Treating Cerebral Venous Sinus Stenosis. Technical Report - Qureshi, Adnan I. (J Vasc Interv Neurol, 2016)
OBJECTIVE: To report upon technique of concurrent placement of angioplasty balloon at the internal jugular vein and sigmoid venous sinus junction to facilitate stent delivery in two patients in whom stent delivery past the jugular bulb was not possible. CLINICAL PRESENTATION: A 21-year-old woman and a 41-year-old woman with worsening headaches, visual obscuration or diplopia were treated for pseudotumor cerebri associated with transverse venous stenosis. Both patients had undergone primary angioplasty, which resulted in improvement in clinical symptoms followed by the recurrence of symptoms with restenosis at the site of angioplasty. INTERVENTION: After multiple attempts at stent delivery through jugular venous bulb were unsuccessful, a second guide catheter was placed in the ipsilateral internal jugular vein through contralateral femoral venous approach. A 6 mm × 20 mm (left) or 5 × 15 mm (right) angioplasty balloon was placed across the internal jugular vein and sigmoid sinus junction and partially inflated until the inflation and relative straightening of the junction was observed. In both patients, the internal jugular vein and sigmoid sinus junction was successfully traversed by the stent delivery system in a parallel alignment to inflated balloon. Balloon mounted stent was deployed at the site of restenosis with near complete resolution of lumen narrowing delivery and improvement in clinical symptoms. CONCLUSION: We report a technique for realignment and diameter change with concurrent placement and partial inflation of angioplasty balloon at the jugular venous bulb to facilitate stent delivery into the sigmoid and transverse venous sinuses in circumstances where multiple attempts at stent delivery are unsuccessful.